2020
DOI: 10.3389/fmed.2020.00222
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy of Routinely Administered Belimumab on Proteinuria and Neuropsychiatric Lupus

Abstract: Background and Objectives: Belimumab (BEL) is a monoclonal antibody approved for the treatment of active systemic lupus erythematosus (SLE) but not for lupus nephritis (LN) and neuropsychiatric systemic lupus erythematosus (NPSLE). We aimed to assess BEL's effects on these severe, potentially life-threatening manifestations. Methods: Retrospective observational cohort study using routine clinical data in a case series of patients with SLE receiving BEL. Results: Sixteen patients received BEL therapy for active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
9
0
1
Order By: Relevance
“…Belimumab, a monoclonal antibody against B‐cell activating factor (BAFF), is the first specific drug approved for the treatment of both SLE 4,5 and LN 6 . The literature describing the effects of belimumab in patients with refractory NPSLE remains scarce 7–9 . While the results of further prospective clinical trials are eagerly awaited, a post hoc analysis of the available phase 3 trials of lupus patients with a headache at baseline concluded in favor of belimumab 10 ; two further studies and our case are consistent with this finding 7,8 .…”
Section: Discussionsupporting
confidence: 76%
“…Belimumab, a monoclonal antibody against B‐cell activating factor (BAFF), is the first specific drug approved for the treatment of both SLE 4,5 and LN 6 . The literature describing the effects of belimumab in patients with refractory NPSLE remains scarce 7–9 . While the results of further prospective clinical trials are eagerly awaited, a post hoc analysis of the available phase 3 trials of lupus patients with a headache at baseline concluded in favor of belimumab 10 ; two further studies and our case are consistent with this finding 7,8 .…”
Section: Discussionsupporting
confidence: 76%
“…Unfortunately, however, NPSLE is not an approved indication for belimumab and it has not been assessed in the management of central nervous system symptoms. Notwithstanding that, a retrospective observational cohort study by Plüß M et al found a favorable effect of belimumab on neuropsychiatric symptoms in patients with severe NPSLE (Plüß et al, 2020). Rituximab is a chimeric monoclonal antibody with a human IgG1 structural domain and a murine CD20 variable region that binds specifically to the B-cell marker CD20 antigen on the cell membrane and belongs to a classical B-cell clearance therapy.…”
Section: Management and Treatmentmentioning
confidence: 99%
“…achieved lasting remission and CRR Fontana F 98 2018 case report 1 proteinuria, C3/C4, anti-dsDNA - CS, CYC, TAC (all discontinued) induction treatment of LN with CS and CYC resulted in severe cryptococcal meningitis and was discontinued; TAC poorly tolerated; off-label BEL for LN resulted in reduced proteinuria, normalized C3/4, and anti-dsDNA titer; no further complications Furie R 23 2020 RCT phase III BLISS-LN 448 PERR at 104w - SoC significantly more pts. achieved PERR or CRR with BEL; lower risk of renal-related event (ESRD, doubling of creatinine) or death Plüß M 79 2020 case series 6 proteinuria over time in preexistent LN - CS + MMF 6 pts. with BEL for SLE and LN at baseline; all had a reduction of proteinuria to various degrees; no new LN flares Binda V 99 2020 case series 17 proteinuria over time in preexistent LN - SoC proteinuria normalized in 3 and improved in 13 pts.…”
Section: The Product Of Interestmentioning
confidence: 99%